Photoacoustic spectroscopy investigation of sintered zinc-tin-oxide ceramics - Ivetić Tamara B.; Nikolić Vesna Maria P.; Pavlović Vladimir B.; Nikolić Pantelija M.; Ristić Momčilo M. (Hemijska Industrija, 2007)
In this paper the changes that occurred in differently activated ZnO-SnO2 and sintered samples were investigated using photoacoustic spectroscopy. ZnO and SnO2 powders, mixed in the molar ratio 2:1, were mechanically activated in a planetary ball mill for 10-160 min. The mixtures were pressed and isothermally sintered at 1300°C for two hours. X-ray diffraction analysis of the obtained sintered samples was performed in order to investigate changes of the phase composition and confirmed only the presence of a pure zinc stannate (Zn2SnO4) phase in all the sintered samples as a result of the solid state reaction and reaction sintering between the starting ZnO and SnO2 powders. The microstructure of the sintered samples was examined by scanning electron microscopy and showed that mechanical activation leads to the formation of a structure with reduced particle size which accelerates spinel formation. Grain growth of the spinel phase slows down the densification process and together with the agglomerates formed during mechanical activation causes the appearance of a porous microstructure. The photoacoustic (PA) phase and amplitude spectra of the sintered samples were recorded as a function of the chopped frequency of the laser beam used (red laser with a power of 25 mW, λ=632 nm) in a thermal-transmission detection configuration. PA experimental data were analyzed using the Rosenzweig-Gersho thermal-piston model, which enabled determination of the thermal diffusivity, Z)T (m2s-1), diffusion coefficient of the minority free carriers D (m2s-1) and the optical absorption coefficient (m-1). The detected differences of the measured thermal-electrical properties of the obtained Zn2SnO4 ceramics indicate changes in the material induced by the different preparation procedure of the starting powders before the sintering process.